KAJIAN TERHADAP PENGALIHAN HAK TANGGUNGAN YANG TIDAK BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 4 TAHUN 1996 TENTANG HAK TANGGUNGAN ATAS TANAH BESERTA BENDA-BENDA YANG BERKAITAN DENGAN TANAH (Studi Kasus antara PT. Bank Jtrust Indonesia Tbk, PT. Asuransi Sinar Mas Tbk dan PT. Maneo Capital Indonesia) - Atikah, Muhana; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Mortgage rights are security rights that are imposed on land rights as referred to in Law Number 5 of 1960 concerning Basic Agrarian Regulations, including or not including other objects that are an integral part of the land, for the settlement of certain debts, which gives priority to certain creditors over other creditors as regulated in Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA), Article 1 point (1) of Law of the Republic of Indonesia Number 4 of 1996 concerning Mortgage on Land and Objects Related to Land (UUHT). However, the existence of the deed of agreement for the transfer of receivables will not be binding or will give any legal consequences to cessus (debtor) if the cessus (debtor) transfer of receivables has not been notified to cessus (debtor) or in writing is not recognized or approved by cessus (debtor as well as the transfer). Mortgage rights must be registered by the new creditor to the land office as referred to in Article 16 paragraph 1 UUHT. Based on these problems the author is interested in knowing first, what is the reason for the transfer of land rights between PT. Bank Jrust Indonesia Tbk, PT. Asuransi Sinar Mas Tbk. and PT. Maneo Capital Indonesia?Secondly, what can be done by the aggrieved party regarding the transfer of land rights between PT. Bank Jrust Indonesia Tbk, PT. Asuransi Sinar Mas Tbk and PT. Maneo Capital Indonesia?This type of research is classified as a sociological legal research. In normative legal research, the data sources are primary data sources and secondary data sources consisting of primary legal materials, secondary legal materials and tertiary legal materials. The collection of normative legal research data uses data collection techniques by means of interviews, questionnaires and literature studies. The data obtained through the literature study will be analyzed qualitatively. In drawing conclusions, the author uses deductive thinking methods, namely a way of thinking that draws conclusions from a general statement or proposition into a specific statement.Keywords: Transfer – Mortgage – Cessie